Kampanye Public Relations tentang Sosialisasi Layanan Elektronik PASTI Kantor Pertanahan Kota Bandung - Widiastuti, Widiastuti; Wahyudin, Aep; Paryati, Paryati (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2020)
This study aims to describe the activities of the Public Relations about the Socialization of Electronic Services PASTI Bandung City Land Office starting from the problem identification stage, the management stage which consists of planning and implementation to the evaluation stage. The results showed that the activities of the Public Relations on the Socialization of Electronic Services PASTI Bandung City Land Office implemented three campaign stages, namely: (1) Problem identification. (2) Campaign management is through the planning process by determining the objectives, target public, actors, messages, and campaign media, and the implementation process is carried out by direct and indirect socialization. (3) Evaluation is carried out by observing changes in the increase that occur in the use of the PASTI application service and changes in community attitudes.